(untitled) (Research, Society and Development, 2022)
Obstetric violence is a form of physical or verbal violence, practiced against pregnant women in health units in the pregnancy-puerperal period, being a serious public health problem in recent decades, due to maternal and child consequences arising from diseases, dysfunctions and psychological disorders caused in women. The objective of the study is to analyze the scientific evidence about the social view of women about obstetric violence and the facts that cause this type of violence. It is based on a study, which emphasizes "Obstetric Violence", "Labor", "Women’s Health", the "fundamental rights of women", among them, the right to life, to privacy, security, equality, freedom of thought, the right not to be subjected to torture, among others.” and “Social Perception”. It relates the dissatisfaction of postpartum women moments before, during or after labor. Being the unsatisfactory, characterized as disrespectful to pregnant women, caused by health professionals, with little or not even some possibility of physical or moral force on their own body, disrespect for their social role as a mother, offenses, submission to the health professional , excessive digital examination, unwanted application of oxytocin, episiotomy, Kristeller maneuver, unwanted cesarean delivery, these and many others. Finally, the study reveals the importance of minimizing and even definitively ending practices that are harmful to the health of the pregnant woman, duly practiced by health professionals during or after the puerperal pregnancy cycle.